Respuesta :

For the first part:

Every shirt she grabs, will cost her dollars, so if she grabs 3 shirts, then the cost of the shirts is:

[tex]12+12+12=3(12)[/tex]

With the same rationale, if she grabs 2 pairs of jeans, the cost of the jeans is:

[tex]19+19=2(19)[/tex]

So, her total is:

[tex]3(12)+2(19)[/tex]

If you subtract 3 from the total, then the expression is:

[tex]3(12)+2(19)-3=36+38-3=71[/tex]

For the second part:

If she's paying 3 less for each shirt, then the cost of 3 shirts will become:

[tex](12-3)+(12-3)+(12-3)=3(12-3)[/tex]

In the same fashion, for the two jeans:

[tex](19-3)+(19-3)=2(19-3)[/tex]

So the expression for the total cost is:

[tex]3(12-3)+2(19-3)=36-9+38-6=59[/tex]

For number three:

The amounts are different because the cost of the total purchase is different than the cost of each element that makes up the total purchase.

For number four:

If you're the owner, you want to give the smallest amount of discount (the one in part 1/a).

So you could clarify by saying there's 3 dollars of the TOTAL purchase's cost.

Otras preguntas